Contributo para o "corpus" artefactual metálico do Bronze Final em território português: a pregaria: DOI: 10.5281/zenodo.12732071 - Melo, Ana Ávila de; Cardoso, João Luís (Estudos Arqueológicos de Oeiras, 2024)
In this article the authors present for the first time two types of nails with long stems from two Late Bronze Age sites in Estremadura, western Portugal. More recently another nail with long stem and a gold conic head was found in a site in southern Portugal of the same age. The rarity of this type of artifacts justified its characterization, which has now been realized.